Comparative role of disc degeneration and ligament failure on functional mechanics of the lumbar spine. Issue 9 (3rd July 2016) - Ellingson, Arin M.; Shaw, Miranda N.; Giambini, Hugo; An, Kai-Nan
Abstract: Understanding spinal kinematics is essential for distinguishing between pathological conditions of spine disorders, which ultimately lead to low back pain. It is of high importance to understand how changes in mechanical properties affect the response of the lumbar spine, specifically in an effort to differentiate those associated with disc degeneration from ligamentous changes, allowing for more precise treatment strategies. To do this, the goals of this study were twofold: (1) develop and validate a finite element (FE) model of the lumbar spine and (2) systematically alter the properties of the intervertebral disc and ligaments to define respective roles in functional mechanics. A three-dimensional non-linear FE model of the lumbar spine (L3-sacrum) was developed and validated for pure moment bending. Disc degeneration and sequential ligament failure were modelled. Intersegmental range of motion (ROM) and bending stiffness were measured. The prediction of the FE model to moment loading in all three planes of bending showed very good agreement, where global and intersegmental ROM and bending stiffness of the model fell within one standard deviation of the in vitro results. Degeneration decreased ROM for all directions. Stiffness increased for all directions except axial rotation, where it initially increased then decreased for moderate and severe degeneration, respectively. Incremental ligament failure produced increased ROM and decreased stiffness. This effect was much more pronounced for all directions except lateral bending, which is minimally impacted by ligaments. These results indicate that lateral bending may be more apt to detect the subtle changes associated with degeneration, without being masked by associated changes of surrounding stabilizing structures.